ANALISIS KUALITAS PRODUK MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL PADA USAHA MIKRO OBAT TRADISIONAL DI BANYUWANGI - kukuh handojo (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2023)
This research aims to analyze product quality in Traditional Medicine Micro Businesses in Purwoharjo District and Srono District whether it is under control or not under control and to find the cause of product damage (defects) of the Traditional Medicine Micro Business. In this study the analysis method used is Statistical Quality Control, which is a statistical method used to solve problems used to analyze, improve products and processes using statistical methods. This research is a type of quantitative research using data collection techniques through observation, interviews, and documentation. Data collection uses a retrospective method. The data analysis used is check sheet, control diagram, and pareto diagram. The results of this study indicate that product quality control at UMOT is still not under control, with an average damage to UMOT A liquid jamu of 3.34% in 3 months, UMOT B liquid jamu of 45% in 3 months, and UMOT C liquid jamu of 41% in 3 months. The most common type of damage was shrunken packaging with 123 bottles of liquid jamu UMOT C and 120 bottles of liquid jamu UMOT B in 3 months, October-December 2022. From the results of observations and interviews in the field, the factors that cause the damage are: the material is a used bottle.